2016
DOI: 10.1016/j.ebiom.2016.07.031
|View full text |Cite
|
Sign up to set email alerts
|

The Non-Linear Child: Ontogeny, Isoniazid Concentration, and NAT2 Genotype Modulate Enzyme Reaction Kinetics and Metabolism

Abstract: N-acetyltransferase 2 (NAT2) catalyzes the acetylation of isoniazid to N-acetylisoniazid. NAT2 polymorphism explains 88% of isoniazid clearance variability in adults. We examined the effects of clinical and genetic factors on Michaelis-Menten reaction kinetic constants of maximum velocity (Vmax) and affinity (Km) in children 0–10 years old. We measured the rates of isoniazid elimination and N-acetylisoniazid production in the blood of 30 children. Since maturation effects could be non-linear, we utilized a pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…396,397 In children, age is an important determinant of pharmacokinetic variability, based on changes in organ size and physiological maturation, including that of enzymes responsible for xenobiotic metabolism. [398][399][400][401][402][403] Furthermore, variation exists from day to day in the same patient, which is termed inter-occasion variability. Thus, a given dose of a drug (even when given in mg/kg rather than an absolute concentration) will achieve many different peak concentrations (C max ) and area under the curve (AUC) values, as well as different lengths of time for which the drug concentration persists above the MIC (T MIC ).…”
Section: Pharmacokinetic-pharmacodynamic Factors In Drug-resistant Tumentioning
confidence: 99%
“…396,397 In children, age is an important determinant of pharmacokinetic variability, based on changes in organ size and physiological maturation, including that of enzymes responsible for xenobiotic metabolism. [398][399][400][401][402][403] Furthermore, variation exists from day to day in the same patient, which is termed inter-occasion variability. Thus, a given dose of a drug (even when given in mg/kg rather than an absolute concentration) will achieve many different peak concentrations (C max ) and area under the curve (AUC) values, as well as different lengths of time for which the drug concentration persists above the MIC (T MIC ).…”
Section: Pharmacokinetic-pharmacodynamic Factors In Drug-resistant Tumentioning
confidence: 99%
“…Glutathione conjugation is already at a relevant level of activity at birth (65% to 70% of the adult level) and is of clinical relevance for paracetamol detoxification . Based on isoniazid in vivo observations, relevant phenotypic acetylation activity and the impact of the different polymorphisms (slow, intermediate, and rapid acetylators) have been described in infants …”
Section: Drug Metabolismmentioning
confidence: 99%
“…85 Based on isoniazid in vivo observations, relevant phenotypic acetylation activity and the impact of the different polymorphisms (slow, intermediate, and rapid acetylators) have been described in infants. 86 The UGTs are responsible for the glucuronidation of hundreds of hydrophobic endogenous compounds and drugs, including morphine or chloramphenicol (both UGT2B7), propofol (UGT1A9), and acetaminophen (UGT1A6/1A9). In vitro ontogeny data are limited 87,88 : in fetal liver samples, activities were low (1% to 10% of adult levels) for UGT1A1, UGT1A3, UGT2B6, UGT2B15, and UGT2B17, 30 whereas after birth, UGT1A9 and UGT2B4 activities remained significantly lower in infants (0.5-2 years) than in older children and adults.…”
Section: Maturational Changes Throughout Childhoodmentioning
confidence: 99%
“…Furthermore, NAT2 protein and activity were detected in term placentas, suggesting potential for placental metabolism of hydralazine . Fetal metabolism of hydralazine has not been shown, but a pediatric study using isoniazid (another NAT2 substrate) reported lower NAT2 activity in neonates compared with older children . Although the fetal metabolism contribution to overall maternal hydralazine PK is expected to be small, fetal metabolism can play a role in enhancing toxicity or minimizing adverse effects of drugs and toxins in the fetus.…”
Section: Discussionmentioning
confidence: 99%
“…58 Fetal metabolism of hydralazine has not been shown, but a pediatric study using isoniazid (another NAT2 substrate) reported lower NAT2 activity in neonates compared with older children. 59 Although the fetal metabolism contribution to overall maternal hydralazine PK is expected to be small, fetal metabolism can play a role in enhancing toxicity or minimizing adverse effects of drugs and toxins in the fetus. Although published data is conflicting, 60 Shi et al reported that following in utero exposure to maternal smoking, there was a decreased risk of orofacial clefts in fetuses that expressed low-activity NAT2 variants.…”
Section: Discussionmentioning
confidence: 99%